2011
DOI: 10.5194/hess-15-1355-2011
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring seasonal climate forecasts for hydropower operations

Abstract: Abstract. Integration of seasonal precipitation forecasts into water resources operations and planning is practically nonexistent, even in regions of scarcity. This is often attributable to water manager's tendency to act in a risk averse manner, preferring to avoid consequences of poor forecasts, at the expense of unrealized benefits. Convincing demonstrations of forecast value are therefore desirable to support assimilation into practice. A dynamically linked system, including forecast, rainfall-runoff, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Short-term weather forecasts (1-7 days) have commonly been coupled with rainfall-runoff models to forecast flood events and plan operational responses (Saavedra Valeriano et al, 2010). By contrast, seasonal climate forecasts (1-6 month) are more commonly used to inform long-term allocation decisions, for instance, by curtailing releases prior to a forecasted drought to conserve water supplies (e.g., Anghileri et al, 2016;Block, 2011;Golembesky et al, 2009). The combination of short-and long-term forecasts has also proven useful (Denaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term weather forecasts (1-7 days) have commonly been coupled with rainfall-runoff models to forecast flood events and plan operational responses (Saavedra Valeriano et al, 2010). By contrast, seasonal climate forecasts (1-6 month) are more commonly used to inform long-term allocation decisions, for instance, by curtailing releases prior to a forecasted drought to conserve water supplies (e.g., Anghileri et al, 2016;Block, 2011;Golembesky et al, 2009). The combination of short-and long-term forecasts has also proven useful (Denaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Combining seasonal meteorological forecasts with hydrological models at continental-scale has provided several continental-scale seasonal hydro-meteorological forecasting systems [22][23][24], such as the European Flood Awareness System [25], the Australian Government Bureau of Meteorology Seasonal Streamflow Forecasts [26], and the National Hydrologic Ensemble Forecast Service, USA [27]. Several studies have demonstrated that a skillful streamflow forecast can enhance the efficiency of water allocation systems to manage the trade-off between hydropower, irrigation, municipal, and environmental services [28][29][30][31]. The potential for employing seasonal forecast in the Yangtze River basin has been investigated in several research studies, mostly through statistical techniques [32][33][34].…”
mentioning
confidence: 99%
“…Several studies of hydropower systems have assessed the improvements in generation and/or revenue from improvements in forecasting local hydrologic state variables, using stochastic dynamic programming [ Stedinger et al ., ; Barnard , ; Tejada‐Guibert et al ., ; Kim and Palmer , ]. Later hydropower studies turned to assessing the value of improvements in seasonal forecasting using climatic teleconnection variables such as sea surface temperatures, in addition to local phenomena, using simulation [ Hamlet et al ., ; Maurer and Lettenmaier , ] and optimization [ Proveda et al ., ; Block , ]. These studies indicate that potential benefits vary widely, depending on local characteristics of the system.…”
Section: Introductionmentioning
confidence: 94%